Rehabilitation: the chronic phase - Kalra, Lalit (Henry Stewart Talks, 2008)
The consequences of stroke, Priorities in rehabilitation, Prevention of complications, Recovery and neuroplasticity, Process of rehabilitation, Interventions in stroke rehabilitation, Organization of multidisciplinary care
Archived at 2018/12/10